A case of liver abscess co-infected with Desulfovibrio desulfuricans and Escherichia coli and review of the literature. Issue 5 (May 2018) - Yamazaki, Tomoo; Joshita, Satoru; Kasuga, Eriko; Horiuchi, Kazuki; Sugiura, Ayumi; Fujimori, Naoyuki; Komatsu, Michiharu; Umemura, Takeji; Matsumoto, Akihiro; Tanaka, Eiji
Abstract: A 73-year-old woman was admitted with consciousness disturbance following a fever. Abdominal computed tomography revealed a large liver abscess with which the presence of Desulfovibrio desulfuricans and Escherichia coli was confirmed by thorough blood and abscess content culture. Empiric meropenem treatment was switched to cefoperazone/sulbactam, followed by ampicillin/sulbactam based on susceptibility testing. Desulfovibrio desulfuricans is a common bacterium that rarely causes liver abscess and may be overlooked during co-infection due to overgrowth of the accompanying bacteria. Clinicians should bear Desulfovibrio desulfuricans in mind and select the appropriate antibiotics according to susceptibility testing when anaerobic bacteria are detected in a liver abscess.